Numerical study on attitude and altitude control of multi-rotor rotorcrafts - Lim, Ann (2012)
UAV is an acronym for Unmanned Aerial Vehicle, which is an aircraft with no pilot on board. UAVs can be remote controlled by a pilot at a ground control station, or it can fly autonomously based on pre-programmed flight plans or more complex dynamic automation systems. UAVs are widely used for a number of missions,including reconnaissance and attack roles. Motivation that drives UAVs research is due to its usefulness in many industries, such as agriculture, telecommunications, and military and also to overcome major challenges faced by designer especially in aspect of design and control strategy.The research carried out is in this thesis is to design quadrotor and trirotor prototype for flight behavior study. The main mission profile for the rotorcrafts is to stabilize at certain altitude and attitude. There are two specific objectives for this study, first is to develop simulations which including dynamic for quadrotor and trirotor systems with given parameters; second is to stabilize the systems by applying controller on each subsystem and tune it to meet stability requirements. Stability is evaluated in aspect of rise time, settling time, overshoot and steady-state error. The previous works of other researchers in multirotor rotorcraft are studied. Quadrotor and trirotor designed by other researchers are used as reference for developing simulation using Matlab Simulink. Control techniques are penetrated intensely for their applications, advantages and weakness. Equations of motion,actuator dynamics and controller equations are figured out and modified reasonably. Controller tuning are carried out to obtain optimum gain which can compensate system error and perform multiple task action. Controller gain is then manipulated to examine behavior of the system. Comparisons with other researchers work are presented. Weaknesses of systems are identified and some suggestions are proposed to improve the system.